"Hey, Mayors, Leave Them Kids Alone": Entrepreneurial Citizens, Policy Noncompliance, and Local Government Response. (May 2014) - Gofen, Anat; Bresler-Gonen, Rotem; Golan-Hoss, Esti
Citizens' local initiatives that are inconsistent with current policy challenge local authorities to act in response. How does local government react and what considerations are involved? Analysis draws on a recent trend in Israel: Dissatisfied parents have been establishing schools even though legal mechanisms enabling such initiatives are absent and central government continues to resist. Findings indicate that local authority reaction is a continuing process, constituting a series of responses. Influenced by societal, operational, and professional considerations, this evolving reaction illuminates that local authorities have been trapped between responsiveness to their communities, compliance with central policy, and maintenance of existing local services.